Collisionless Magnetic Reconnection and Waves: Progress Review - Khotyaintsev, Yuri V.; Graham, Daniel B.; Norgren, Cecilia; Vaivads, Andris (Frontiers in Astronomy and Space Sciences, 2019)
Magnetic reconnection is a fundamental process whereby microscopic plasma processes cause macroscopic changes in magnetic field topology, leading to explosive energy release. Waves and turbulence generated during the reconnection process can produce particle diffusion, and anomalous resistivity, as well as heat the plasma and accelerate plasma particles, all of which can impact the reconnection process. We review progress on waves related to reconnection achieved using high resolution multi-point in situ observations over the last decade, since early Cluster and THEMIS observations and ending with recent Magnetospheric Multiscale results. In particular, we focus on the waves most frequently observed in relation to reconnection, ranging from low-frequency kinetic Alfven waves (KAW), to intermediate frequency lower hybrid and whistler-mode waves, electrostatic broadband and solitary waves, as well as the high-frequency upper hybrid, Langmuir, and electron Bernstein waves. Significant progress has been made in understanding localization of the different wave modes in the context of the reconnection picture, better quantification of generation mechanisms and wave-particle interactions, including anomalous resistivity. Examples include: temperature anisotropy driven whistlers in the flux pileup region, anomalous effects due to lower-hybrid waves, upper hybrid wave generation within the electron diffusion region, wave-particle interaction of electrostatic solitary waves. While being clearly identified in observations, some of the wave processes remain challenging for reconnection simulations (electron Bernstein, upper hybrid, Langmuir, whistler), as the instabilities (streaming, loss-cone, shell) which drive these waves require high resolution of distribution functions in phase space, and realistic ratio of Debye to electron inertia scales. We discuss how reconnection configuration, i.e. symmetric versus asymmetric, guide-field versus antiparallel, affect wave occurrence, generation, effect on particles, and feedback on the overall reconnection process. Finally, we outline some of the major open questions, such as generation of electromagnetic radiation by reconnection sites and role of waves in triggering/onset of reconnection.